Retained Ureteral Stents at a Tertiary Referral Stone Center—Who is at Risk?. Issue 6 (November 2018) - Jain, Rajat; Chaparala, Hemant; Omar, Mohamed; Ganesan, Vishnu; Sivalingam, Sri; Noble, Mark; Monga, Manoj
Abstract : Introduction: : Encrustation of retained ureteral stents can lead to significant morbidity. We examined the treatment of patients with retained stents. Methods: : Patients with retained stents were identified from a prospectively collected stone registry at a high volume center. The electronic medical record was queried using a relational database management program to parse operative notes for the terms "retained" and "encrusted." The generated list was manually validated, and data were collected and analyzed retrospectively. We collected demographics, medical history, insurance type, and surgical and postoperative data. Preoperative degree of encrustation was graded using the forgotten, encrusted, calcified system. A cohort of patients undergoing ureteroscopy for urolithiasis was identified as a control group. Results: : Overall 66 patients with retained, encrusted stents and 4, 962 controls were identified. The indication for stent insertion was most commonly obstructing stone (53%), after ureteroscopy (15%) and after extracorporeal shock wave lithotripsy (11%). There were no differences in age, body mass index or gender distribution. Patients in the encrusted stent group were more likely to have Medicaid or no insurance (p <0.001). Longer indwelling time predicted a higher degree of encrustation (mild—3 months, moderate/severe—9 months, p=0.02) as did prior stone history (mild 57%, moderate 76%, severe 93%, p=0.01). Patients with prior stone history, higher grade encrustation and upper coil encrustation were more likely to require more than 1 procedure for stent clearance (p=0.04, p=0.0001 and p <0.001, respectively). Conclusions: : Encrustation of retained stents is a preventable phenomenon which can lead to significant morbidity. Indwelling time and history of stone disease are predictive of the degree of encrustation. Upper coil encrustation increases complexity of management, more often requiring multiple procedures.